Revitalization of Islamic Story Learning in Islamic Religious Education through the Development of Mind Mapping-Based Teaching Materials - Masrurih; Uthman Shehu Lawal (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to develop Islamic Religious Education (PAI) teaching materials based on Islamic stories with a mind-mapping approach to improve elementary school students’ understanding of religious values . The background of this study is based on the lack of innovative and contextual learning media in PAI learning, especially in Islamic story material. This study uses the Borg and Gall Research and Development (R&D) model, which is simplified into five stages: preliminary study, product design, expert validation, limited trials, and field trials. Data collection techniques include interviews, observations, documentation, and written tests. The results of the study showed that the teaching materials developed were considered very valid by the Material Teacher (score 92%) and Media Teacher (score 88%) and were stated as very practical by teachers (score 91%) and students (score 89%). The effectiveness test showed an increase in the average score from the pretest 65.2 to the posttest 84.7, with the results of the paired sample t-test of Sig. (2-tailed) = 0.000. This study has implications for strengthening Islamic Religious Education learning in line with the principles of the Independent Curriculum, namely active, reflective, and meaningful learning.